Accuracy of older adults in judging self-generated elbow torques during multi-joint isometric tasks - Cai, Ninghe M.; Dewald, Julius P. A.; Gurari, Netta (Scientific reports, 2020)
Successful execution of daily activities requires accurate perception of the torques one generates about multiple joints. Even so, previous studies are mostly limited to an individual’s perception when torques are generated about a single joint. Consequently, this study investigates how accurately individuals judge torques at their arm during a multi-joint task. The accuracy of fifteen right-hand dominant participants (age: 60 ± 10 years) in matching isometric elbow torques, within the same arm, was quantified during single- and/or multi-joint tasks. Participants generated and matched elbow torques when the shoulder was: (1) not abducted (single-to-single-joint), (2) abducted (multi-to-multi-joint), and (3) abducted and then not abducted (multi-to-single-joint). The constant error for the multi-to-single-joint condition (dominant: 6.9 ± 5.9 Nm, non-dominant: 6.0 ± 5.5 Nm) was greater than that for the single-to-single-joint condition (dominant: 2.7 ± 3.1 Nm, non-dominant: 3.4 ± 2.8 Nm) (p < 0.001) and multi-to-multi-joint condition (dominant: 3.0 ± 2.8 Nm, non-dominant: 3.9 ± 2.7 Nm) (p < 0.001). The constant error for the multi-to-multi-joint condition did not significantly differ from that of the single-to-single-joint condition (p = 0.780). Findings indicate that in older adults the perception of a self-generated torque during a 2-degree-of-freedom (DOF), multi-joint task is largely influenced by the motor commands associated with the 2-DOF task and is not specific to the DOF at each joint.